GeoGebra, recurso computacional a favor da aprendizagem matemática no ensino fundamental II - Selli, Luis Fernando (2014)
This paper is related to the application of GeoGebra software in the following topics: Ratio, Proportion, Thales Theorem, Similarities, Similarity of Triangles, Pythagorean Theorem, Trigonometric Ratios in the Triangle Rectangle, Number and circumference. Initially all the contents were thought by traditional method, board and chalk. Therefore the GeoGebra software was applied. It was developed to teachers and students (9th grade) of an elementary school involved in these activities. Positive and negative results were showed but there is a perspective of improvement. All the stages are separately related to help the understanding. The object is the analyses about the importance and relevancy of using computerized mathematical tools during the learning process.